New Statistical Metrics for Multisite Replication Projects. (21st May 2020) - Mathur, Maya B.; VanderWeele, Tyler J.
Summary: Increasingly, researchers are attempting to replicate published original studies by using large, multisite replication projects, at least 134 of which have been completed or are on going. These designs are promising to assess whether the original study is statistically consistent with the replications and to reassess the strength of evidence for the scientific effect of interest. However, existing analyses generally focus on single replications; when applied to multisite designs, they provide an incomplete view of aggregate evidence and can lead to misleading conclusions about replication success. We propose new statistical metrics representing firstly the probability that the original study's point estimate would be at least as extreme as it actually was, if in fact the original study were statistically consistent with the replications, and secondly the estimated proportion of population effects agreeing in direction with the original study. Generalized versions of the second metric enable consideration of only meaningfully strong population effects that agree in direction, or alternatively that disagree in direction, with the original study. These metrics apply when there are at least 10 replications (unless the heterogeneity estimate τ ^ = 0, in which case the metrics apply regardless of the number of replications). The first metric assumes normal population effects but appears robust to violations in simulations; the second is distribution free. We provide R packages (Replicate and MetaUtility).